OIL AND GAS REVENUE ACCOUNTING TREATMENT AND COMPLIANCE: SYSTEMATIC REVIEW OF UPSTREAM COMPANY PRACTICES - Meila, Al Ahda Nafasya; Namira, Putri Rahma; Destari, Ryanti; Henda Safitri, Rika; Wahyudi, Tertiarto; Hamzah, Ruth Samantha (Jurnal Cakrawala Akuntansi, 2026)
The upstream oil and gas sector faces escalating complexity in revenue accounting treatment due to evolving international standards (PSAK 64/IFRS 15), substantial capital investments, reserve uncertainty, and intensifying climate-related asset valuation challenges, yet systematic evidence on implementation practices and compliance effectiveness across diverse institutional contexts remains fragmented. This study aims to comprehensively analyze revenue accounting treatment practices, evaluate compliance levels with financial accounting standards, map implementation challenges, and identify critical research gaps in upstream oil and gas companies through systematic literature review methodology. Following the PRISMA protocol, this research systematically searched four major academic databases Scopus, Web of Science, ProQuest, and ScienceDirect using predefined keywords, ultimately selecting 10 high-quality studies published between 2021-2025. The findings reveal that proper revenue accounting treatment is critical given the substantial global revenue magnitude and concentrated profit distribution patterns. Implementation of industry-specific accounting standards significantly enhances capital allocation efficiency, reduces information asymmetry, and positively impacts performance metrics. However, critical implementation challenges persist in three areas: absence of unified decommissioning accounting standards, inadequate frameworks for stranded asset valuation amid potential US$13-17 trillion devaluations, and insufficient transparency mechanisms for profit distribution reporting. This study contributes by providing systematic evidence synthesis across diverse geographical contexts, identifying prioritized research gaps in asset valuation frameworks and decommissioning standards, and offering actionable recommendations for standard setters to develop industry-specific guidance, regulators to strengthen enforcement mechanisms, and academics to pursue longitudinal comparative research examining climate risk integration in financial reporting practices.